Performance evaluation and enhancement of EDCA protocol to improve the voice capacity in wireless network - Abu-Khadrah, Ahmed Ismail Mohammad (2017)
Enhanced Distributed Channel Access (EDCA) protocol is used to support quality of service (QoS). However, using the default parameter values for EDCA protocol leads to increasing the collisions in the wireless network and decreasing the capacity. This is due to the default EDCA protocol gives the access point and wireless stations the same priority to access the medium, in spite of the access point has high load traffic compared with normal wireless stations. Therefore, in this research work a new algorithm was proposed to enhance the capacity of the EDCA protocol and increase the number of the active voice users. The idea of the algorithm was based on creating different contention window ranges between access point and wireless workstations, and changing the technique of increasing the contention window value when the collision happened. Through the proposed algorithm, the Minimum Contention Window (CWmin) and Arbitration Inter Frame Space (AIFS) parameters were adapted based on the percentage of the collision in the network. By applying the proposed algorithm, the throughput of EDCA protocol was increased by 42.9% and it can support 14 voice users rather than 11 in the default EDCA protocol. The QoS requirements were achieved when the network contained 14 voice users. The end to end delay became 86.44 ms and the packet loss percentage was 0.06 %. In addition to that the uplink and downlink voice throughputs covered the data rate requirements. Moreover, a new mathematical model was designed based on the Markov chain mechanism in order to evaluate the performance of the EDCA protocol under saturation and non saturation conditions, which aimed to separate between the uplink and downlink throughputs with different data types. The separation between uplink and downlink throughputs is based on separating the model equations between the access point and the stations. This separation contributes in determining the effect of access point on the network performance as well as it allows in evaluating the algorithms that based on the differentiation between the access point and stations. The OPNET simulator and the mathematical model were used to evaluate the performance for the proposed algorithm. Therefore, by applying the proposed algorithm, the collisions in network will be decreased and leading to the enhancement of the network capacity. It is believed that this study is useful to cover more voice users in the public wireless network that deployed in bus stations, restaurants, parks, airports and etc.